Kedudukan As-Sunnah sebagai Sumber Hukum Islam: Kajian Terhadap Kehujjahan dan Fungsinya dalam Syariat Islam - Muhammad Adham Baehaqi; Norhikmah Norhikmah (Jurnal Teologi Islam, 2026)
This research is motivated by the importance of affirming the position of the Sunnah as a source of Islamic law after the Qur'an, amidst ongoing debate regarding its validity. This article aims to analyze the position of the Sunnah as a source of Islamic law, examine the basis for its validity based on the Qur'an, hadith, consensus of the Companions, and rational evidence, and explain its role in the Qur'an's development of Islamic law. The research uses a qualitative approach with library research through a review of relevant primary and secondary sources, followed by descriptive-analytical analysis using a normative approach. The results indicate that the Sunnah has strong legitimacy as the second source of Islamic law after the Qur'an, both normatively and methodologically. As-Sunnah also functions as a reinforcement (ta'kid) of the provisions of the Al-Qur'an, as an explanation (bayan) for verses that are still global, general, or absolute, as well as forming laws (tasyri') on matters that are not explained explicitly in the Al-Qur'an. Thus, As-Sunnah is an authoritative and integral source of law in the formation and development of Islamic law.